2015
DOI: 10.1016/j.bcmd.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in well-transfused thalassemia major patients

Abstract: The risk for pulmonary hypertension (PH) in thalassemia major (TM) patients remains controversial. We report echocardiography results from 60 TM patients: we evaluated the association between tricuspid regurgitation velocities (TRV), iron stores, and serologic markers of hemolysis and arginine dysregulation. Patients were enrolled from August 2004 until May 2009. All parameters were inversely weighted by the number of exams. TRV was comparable between sexes and it was uncorrelated with age. At the first exam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…This notion may be at the center of the argument of the need to transfuse patients with non-transfusion dependent thalassemia (NTDT) more regularly to avoid or delay PH [28]. Female predominance, though insignificant, among patients with PH in the current study is shared by some reports [29,30], but disputed by others [17][18][19]. Strong female predominance in many forms of PH is well recognized [31].…”
Section: Plos Onementioning
confidence: 60%
See 1 more Smart Citation
“…This notion may be at the center of the argument of the need to transfuse patients with non-transfusion dependent thalassemia (NTDT) more regularly to avoid or delay PH [28]. Female predominance, though insignificant, among patients with PH in the current study is shared by some reports [29,30], but disputed by others [17][18][19]. Strong female predominance in many forms of PH is well recognized [31].…”
Section: Plos Onementioning
confidence: 60%
“…While PH is a well-recognized complication of TM, its doppler-defined frequencies in various TM series showed remarkable variability ranging from 1.7% to 79% [13][14][15][16][17][18][19]. The most important cause of such variability is the choice of the TVR cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…Meloni et al [62] reported echocardiography results from 60 TM patients and evaluated the association between TRV, iron stores, and serologic markers of hemolysis. They concluded that well-transfused TM patients have a lower risk for PH.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported low GAB in thalassaemia compared to normal control subjects (Morris et al , ), however patients were not differentiated by TRV or cardiopulmonary dysfunction. Of interest, Meloni et al () recently published an association of TRV elevation with reduced GAB, together with increased anaemia, cardiac index and diastolic dysfunction in 60 TM patients. We describe, however, the first report to identify excess arginase activity as a key mechanism associated with low GAB in thalassaemia.…”
Section: Discussionmentioning
confidence: 99%